DESIGN OF MULTI-STORY HOTEL BUILDING IN LOAS ANGELES, CALIFORNIA, USA - Dossov, Azamat; Bertebayeva, Kamila; Dyussenbekov, Anuar; Islyambekova, Gulnaz; Seiilkhan, Bagdat; Seilkhan, Shynggys (Nazarbayev University School of Engineering and Digital Sciences, 2025)
In this paper, we present the design and construction of a large-span 16-story luxury hotel with a basement located at 1201 South Grand Avenue, Los Angeles, California in a high seismic zone. The project utilizes a holistic architectural, structural, geotechnical, environmental, and construction engineering design approach to function, safety, and guest experience. The hotel will offer luxury accommodations and a wide range of amenities, including rooftop restaurants, a swimming pool, conference halls, a fitness center, and lounge areas, enhancing overall guest satisfaction. This project features two parking areas which are a 45 × 56 m² outdoor parking facility and an underground parking facility that offers extra space and structural support. This also offers savings from the associated construction stages by integrating the underground parking facility completely into the geotechnical and structural planning, thus creating high stability in the seismically active region. The design includes a storm sewer system to comply with the requirements for drainage and water management. A 2020 GeoPentech investigation for the site — originally to be built with a 40-storey mixed-use building — is used for geotechnical analysis. The design adheres to IBC, ASCE, and LA Building Code standards, with special emphasis on seismic issues at the structural and foundation level. This hotel constitutes an innovative high-end hospitality experience when compared to the existing seismic conditions on site.
Keywords: luxury hotel; Los Angeles; seismic design; structural design; geotechnical analysis; parking design; storm sewer design; construction management; type of access: open access